Ravana fakes the death of Rama and Lakshmana to Seeta. See the two heads on the ground.; Carving on the parapet wall - sequences from the epic Ramayana - Brig. Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in